A study on oral clonidine vis a vis intravenous lignocaine for attenuation of hemodynamic response to laryngoscopy and endotracheal intubation - Roy, Sankar; Gharami, Bidyut Bikas; Pandit, Paramita; Biswas, Arunava; Bhattacharya, Dipasri; Sen, Sukanta (Asian Journal of Medical Sciences, 2021)
Background: Hemodynamic change takes place during procedures like laryngoscopy and endotracheal intubation due to reflex sympathetic discharge caused by epipharyngeal and laryngopharyngeal stimulation before a surgery under general anesthesia. Aims and Objectives: The aim of the study was to compare the effectiveness of oral clonidine and intravenous lignocaine as premedicant to obtund the stress response due to such mandatory maneuvers. Materials and Methods: A prospective, randomized, double-blind, double dummy-controlled study was undertaken for 11 months at a tertiary care hospital in the eastern part of India. A total (n=100) patient aged 30 to 50 years of either sex with ASA I and II waiting for elective abdominal surgery were randomized into two equal groups. Group C (n=50) received (4μg/kg) of oral clonidine 90 minute before laryngoscopy and Group L (n=50) received 1.5 mg/kg lignocaine 3 minute before laryngoscopy as active drugs and appropriate placebos were administered as double dummy technique. Comparable demographic and baseline parameters like heart rate, systolic blood pressure and diastolic blood pressure were recorded at various time intervals. Similar anesthesia technique applied was in both the study arm. Result: Attenuation of systolic blood pressure, diastolic blood pressure, heart rate and mean arterial pressure was statistically highly significant (p<0.0001) more in Group C as compared to Group L within first vital 10 minutes of intubation. Conclusion: Oral clonidine attenuates the stress response better than intravenous lignocaine during laryngoscopy and endotracheal intubation with minimum adverse effects.